Career Competencies, Preparing Students for the Future - Marinka A. C. T. Kuijpers (Social Sciences)
The changing nature of the labor market demands lifelong development of employees. This places a new responsibility on education to prepare students for a future of lifelong development. An important aspect of this preparation is the development of career competencies. Career competencies are examined from different perspectives. Two meta-studies, analyzing 77 and 80 international studies, highlight two key theories for understanding career competency development: the Intelligent Career Theory (ICT) and the Social Cognitive Career Theory (SCCT). This article aims to provide deeper insight into career competencies for students by analyzing them conceptually through various theoretical lenses and linking them to research on educational practice in the Dutch context, where development of career competencies is a mandatory part of the pre-vocational and secondary educational curriculum. The ultimate goal is to develop recommendations for designing a learning environment that fosters career competency development in students.